2018
DOI: 10.1093/milmed/usx182
|View full text |Cite
|
Sign up to set email alerts
|

Healthy Active Duty Military with Lifetime Experience of Mild Traumatic Brain Injury Exhibits Subtle Deficits in Sensory Reactivity and Sensory Integration During Static Balance

Abstract: Postural control and stress reactivity were investigated in active duty coast guard personnel to determine whether they are sensitive to lifetime effects of mild traumatic brain injury (mTBI). A custom-designed and validated virtual reality-based computerized posturography device was used to assess postural stability, whereas emotional reactivity was assessed using the acoustic startle response (ASR), and neurocognitive performance was assessed using the defense-automated neurobehavioral assessment (DANA). It … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 60 publications
0
12
0
Order By: Relevance
“…The sample size for the included clinical studies was consistently low, with the majority ranging from 16 to 66 participants, with only a few moderately sized (111–453 individuals) 32 − 395 − 125 − 125 − 125 − 12 and one large study (4,007 subjects) ( 55 ). The source populations of clinical studies varied widely including rehabilitation institutes ( 22 , 23 , 59 , 67 ), professional athletes ( 25 , 26 ), college students ( 54 , 71 , 78 ), college athletes ( 19 , 60 , 61 , 63 , 68 , 73 , 76 ), military veterans ( 40 , 52 56 , 65 , 69 ), and the community ( 51 , 54 , 58 , 64 , 70 , 72 , 75 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size for the included clinical studies was consistently low, with the majority ranging from 16 to 66 participants, with only a few moderately sized (111–453 individuals) 32 − 395 − 125 − 125 − 125 − 12 and one large study (4,007 subjects) ( 55 ). The source populations of clinical studies varied widely including rehabilitation institutes ( 22 , 23 , 59 , 67 ), professional athletes ( 25 , 26 ), college students ( 54 , 71 , 78 ), college athletes ( 19 , 60 , 61 , 63 , 68 , 73 , 76 ), military veterans ( 40 , 52 56 , 65 , 69 ), and the community ( 51 , 54 , 58 , 64 , 70 , 72 , 75 , 77 ).…”
Section: Resultsmentioning
confidence: 99%
“…We discuss our findings in the context of previous balance control tests for concussion assessment and using the optimal movement variability hypothesis to frame our observations. Previous work has shown that neuromotor dysfunction occurs after a concussion [31,38,39]. Specifically, balance control becomes more variable due to neuromotor sensory integration challenges [32].…”
Section: Discussionmentioning
confidence: 99%
“…Other studies using different posturography assessments have shown people at various recovery times following mTBI with increased postural sway relative to healthy controls when exposed to visual scenes with motion or visual surrounds that moved (13,15,16,19). Balance control requires multisensory processing and it has been theorized that visual-vestibular sensory processing may be impaired acutely after mTBI (51,52).…”
Section: Increased Reliance On Visionmentioning
confidence: 99%
“…Less common are assessments of mTBI-related balance deficits using "stimulus-evoked sway" measures derived from sway responses to stimuli applied to various sensory modalities to identify their influence on balance. For example, larger magnitude CoP sway was evoked in mTBI subjects than healthy controls (HC) when exposed to a rotating visual scene (15)(16)(17). In these studies, increased responsiveness to visual motion was interpreted as indicating abnormal visual-vestibular processing since mTBI subjects apparently had reduced ability to use vestibular orientation cues to suppress the effects of the visual stimulus.…”
Section: Introductionmentioning
confidence: 99%